PERKEMBANGAN SOSIAL EKONOMI MASYARAKAT INDUSTRI KECIL SARUNG TENUN DI DUSUN JAMBU KELURAHAN SEMAMPIR KECAMATAN CERME KABUPATEN GRESIK - RENGGANIS GANDA MILLIAR (Jurnal Pendidikan Ekonomi (JUPE), 2013)
Hamlet of Jambu village of Semampir an industrial area that would be famous. Beforethere small scale industries woven sarongs, the majority of people in this area justwork in the agricultural sector. Because it is considered not sufficient for day-to-day,the people in the hamlet of Jambu village of Semampir started an initiative to changehis fate by way of a small scale industries pioneer woven sarongs. In this researchused qualitative approach. The subjects in this research were much as 10 informants.Determination of research informants using snowball sampling technique. The resultsof this research were (1) Currently at hamlet of Jambu village of Semampir there areat least 21 units of industrial woven sarongs average has elaborated its business forgenerations. In the process of making woven sarongs requires it takes is perseveranceand skill. (2) Small scale industries woven sarongs at hamlet of Jambu village ofSemampir able to improve the socio-economic of community. First, increase incomesof community. Second, improving inter-community social relations. Third, small scaleindustries woven sarongs are also able to provide a high view especially for theparents of their childrens education.Keywords: socio-economic of community and small scale industries